Current likelihood and dynamics of hot summers in the UK. (3rd September 2020) - Kay, Gillian; Dunstone, Nick; Smith, Doug; Dunbar, Tyrone; Eade, Rosie; Scaife, Adam
Abstract: Summer 2018 in the United Kingdom (UK) was its joint hottest on record and the associated impacts raise questions over societal resilience to extremes of this magnitude or greater occurring in upcoming years. Better information on the current likelihood of extreme and unprecedented events feeds into improved understanding of risk, relevant for policy and contingency planning. However, making robust estimates of likelihood is difficult given that extremes in the historical record are few by definition. We overcome this by using a large ensemble of initialised climate model simulations to assess the chance of exceeding summer 2018 temperatures in the current climate and find it to be ∼11% each year, although a weak circulation bias may mean this estimate is conservative. This likelihood has increased sharply over the last few decades. A one in 100-year event would bring summertime temperatures to the UK of approximately 1 °C above 2018, an anomaly similar to that of the notable hot summer of 1976. Subsetting the large ensemble enables characterisation of the dynamics around hot summers, and investigation of possible remote influences. Several circulation patterns bring warm temperatures to the UK, and it is likely that influences from different remote regions are active or dominant in different years. We present evidence suggesting roles for tropical precipitation anomalies via extratropical wave trains. Circulation anomalies associated with wet conditions in the Caribbean project particularly strongly onto the hot UK summer conditions, with a weaker signal from the tropical Pacific consistent with developing La Niña. We also highlight possible influence in some years from springtime high sea ice anomalies in the Sea of Okhotsk and low anomalies in the Barents/Kara seas. Building on this, we use new experiments that isolate the effects of opposing springtime sea ice anomalies in the two regions and find a causal relationship with the summertime circulation over the North Atlantic and northern Europe.